Institutional economics perspectives on African agricultural development - Kirsten, Johann F.; Dorward, Andrew R.; Poulton, Colin; Vink, Nick (International Food Policy Research Institute, 2009)
Professionals in economics and agricultural economics have been paying increasing attention to institutional issues and have developed strong concepts and analytical tools to do so. The core message of this book is that this new focus is particularly relevant to the problems of agricultural development in Africa. As a result, there is a need to consolidate the lessons learned into a textbook to illustrate the relevance and application of these concepts and tools. The core purpose of the book is, therefore, to provide an accessible text on the economics of institutions relevant to agricultural development in the African context. However, the book cannot be regarded as exhaustive: it should be used by the discerning student as a text to be supplemented by the reading lists and the large volume of literature cited throughout the volume.